Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations First of all, the feet must be kept scrupulously clean. Wash them at least once a day, oftener if you can, in warm water. A cold water rinse will help them to resist both heat and cold, and tone up the skin. Wipe them dry, not forgetting between the toes. If they are inclined to perspire, apply methylated spirit, as this hardens and dries the skin. If corns appear, after soaking the feet well, apply a corn cure — a wee drop of vinegar in the centre, if persevered with and applied frequently enough, may eventually cause the core of hardened skin, which causes so much agony, to drop out. Meanwhile keep the hard skin cut down with a safety razor drawn carefully towards you. Cut the nail of the big toe straight across, and the others slightly curved, but do not cut too closely. Give your feet free play and exercise for a few minutes every day by walking about your room in your stockinged feet. Sit down and pretend to play the piano with your toes, and you will be surprised to find how flexible they are. Change your heavy outdoor footwear when you remain indoors for any length of time, to give your feet rest and air. When your feet are hot and sore, rest them on a level with your hips, or even higher, if you can do so without behaving in an unbecoming way, to let the blood drain out of them. Choose your shoes long and broad enough to allow for full expansion of your feet when, in walking, the weight of the body tends to flatten them out, and never condemn the poor things to a size too small for the sake of smartness. Have the heels of walking shoes low and broad, keeping high heels for occasions when you are at rest or for dancing (when the foot is raised naturally). But walking and standing must be firm and secure. [illustration] 7 177/5/8/4